LINGUISTIC AND EXTRALINGUISTIC FACTORS IN THE TRANSLATION OF SPECIAL TEXTS - Shahodat Usmanova; Esirgapova Umida (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the intricate interplay between linguistic and extralinguistic factors in the translation of specialized texts, shedding light on the nuanced skills required for accurate and effective cross-cultural communication.